Negotiating identity through sports and outdoor in Jack London`s fiction - Korzeniewska-Nowakowska, Paulina (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Jack London went down in literary history as a versatile and colourful author. Having drawn from his abundant biography (London was preoccupied with journalism, pouching and gold digging, among others), he became a prominent representative of the "adventurous Romanticism". Critics and readers have also acknowledged and appreciated his considerable input into the tradition of storting writing, as he frequently contextualized the dilemmas he explored in the sporting terrain.
Keywords: sports writing; London, Jack (1876-1916); outdoor